Publisher Correction: A short isoform of ATG7 fails to lipidate LC3/GABARAP. Issue 1 (December 2018) - Ogmundsdottir, M.; Fock, V.; Sooman, L.; Pogenberg, V.; Dilshat, R.; Bindesbøll, C.; Ogmundsdottir, H.; Simonsen, A.; Wilmanns, M.; Steingrimsson, E.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.